2023
DOI: 10.1080/13603124.2023.2274362
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ opinion and experiences of the application of instructional leadership: evidence from history teachers

C. Musandu,
L. C. Jita,
A. A. Bada

Abstract: While there is overwhelming evidence regarding the impact of instructional leadership on student learning and outcomes (Leithwood et al., 2014;Mendels, 2012), there is far less knowledge and little systematic research on how teachers respond to the practice of instructional leadership (Bellibas, 2014;Isaiah & Isaiah, 2014). This study arises out of the concerns that instructional leadership has not received sustained attention from educational researchers in Zimbabwe. Much of the research work in Zimbabwe has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…In America, it had been reported that the quality of school resources such as buildings, finance and qualified teachers were critically important in the quest to improve instructional management outcomes in educational institutions (Musandu, 2017). Good educational learning outcomes depend on crucial resource capacity, such as learning and teaching materials that are conducive (UNESCO, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In America, it had been reported that the quality of school resources such as buildings, finance and qualified teachers were critically important in the quest to improve instructional management outcomes in educational institutions (Musandu, 2017). Good educational learning outcomes depend on crucial resource capacity, such as learning and teaching materials that are conducive (UNESCO, 2016).…”
Section: Introductionmentioning
confidence: 99%